Pengaruh Model Pembelajaran Course Review Horay Berbantuan Permainan Cag-Cag Terhadap Hasil Belajar IPAS Siswa Sekolah Dasar - Sumiantari, Gusti Ayu Komang; Ardiawan, I Ketut Ngurah; Dewi, Ni Putu Candra Prastya (STAHN Mpu Kuturan Singaraja, 2023)
This research will be able to describe differences in student learning outcomes as demonstrated by determining differences in student learning outcomes as demonstrated by the use of learning styles supported by the cag-cag game learning style supported by CRH (Course Review Hooray). This review is a semi-basic assessment with a quantitative experimental approach. In this study, the population was all students in grades IV and VI in Negara District, Jembrana Regency, totaling 215 students. The set of steps used in this research is a semi-analytic framework. Judging from the results obtained, the model in this assessment is class 4 students at SDN 4 Berangbang for the control class and SDN 5 Berangbang as the experimental class. The exploratory strategy in this review relates to information from interviews, different decision tests and documentation. Considering the measurable examination results of autonomous tests and applicable past research, as well as the depiction of hypotheses, experts reasoned that it shows that the science learning outcomes of students who concentrate by implementing Cag Game-Assisted cooperative learning with the Course Review Horay (CRH) model. then it was further developed by students who obtained results from implementing the regular learning model in Class IV Group VI of the State Yudistira Region of Jembrana Regency.